Perspectives and Studies on Instructed Second Language Acquisition - Tangkiengsirisin, Supong (Thammasat Review, 2015)
There have been debates over how grammar should be taught: whether explicit or implicit instruction would yield higher benefit for language learners. This paper discusses studies in SLA with regard to the grammar teaching methods. Although grammar should be taught so that L2 learners can pass through developmental sequences and gain implicit knowledge useful for real-life communication, current research has revealed empirical evidence that certain grammatical structures can be taught explicitly, and formed-focused grammar instruction would be helpful in terms of “noticing” and “consciousness raising”. Keyword: Debate, Communication, Implicit